Evaluation of Uncomplicated Isolated Extensor Tendon Injury Repair of Hand in Amritsar (India) - Kumar, Hemant; Rani, Parul; Banga, Ravider K.; Boparai, Randhir Singh; Singh, Jaspal (Nigerian Journal of Orthopaedics and Trauma, 2018)
Introduction: Extensor tendon injury is one common hand injury occurring in young individuals. Extensor tendons are superficially located with minimal amount of subcutaneous tissue that predisposes the extensor mechanism to more complex tendon injuries. Surgical repair of extensor tendon requires an exact knowledge of anatomy, careful adherence to some basic surgical principles, sound clinical judgment, strict atraumatic surgical technique and a well planned postoperative programme. Aim and Objectives: We conducted this study to find out common causes of extensor tendon injuries, evaluation of hand function after repair of extensor tendon injuries and evaluation of effect of time elapsed between onset of injury to tendon repair on the final outcome. Methodology: The functional outcome after tendon repair was assessed by calculating Total Active range of Motion (TAM). Results: We concluded that the higher percentage of excellent and good cases is might be attributable to strong and meticulous repair in which more aggressive physiotherapy was tolerated by the patients and the tendons should be repaired preferably primarily.